Mapeamento fino de locos associados à resistência à mancha angular em feijão (Phaseolus vulgaris L.) - Oblessuc, Paula Rodrigues, 1981- (2013)
Orientadores: Luciana Lasry Benchimol Reis, Luis Eduardo Aranha Camargo